Bringing anatomy to life: the role of clinical ultrasound in undergraduate medical education – a systematic review - Mathilde Brunel; Valentin Sebastian Schäfer; Florian Recker (The Ultrasound Journal)
Abstract Background The implementation of ultrasound as point-of-care technique within the medical education has been broadly studied to understand its applicability in clinical settings. More research has been conducted to specifically understand the use of clinical ultrasound in the medical curriculum to learn anatomy. The results of publications on anatomical skills and knowledge outcomes of students related to ultrasound are contradictory. The objectives of this study were to identify and describe common study types and educational programs conducted in anatomy teaching with clinical ultrasound and to describe the impact on learning outcomes. Methods A literature search from the databases Scopus, PubMed and Google scholar was conducted with keywords related to anatomy learning, ultrasound and medical education. Data from publications were extracted following quantitative and qualitative methods previously described in the literature and adapted to measure the educational outcome. Results In total, 1615 records were detected within all three databases after removing duplicates, 194 were found relevant to the topic and included in the review. Of 194, 128 articles were original studies categorized by their study types and outcomes. A large proportion of the studies were conducted at a single institute, and students were mainly evaluated with post-tests only or with pre- and post-tests. Vascular and cardiac anatomical landmarks were the most frequently instructed areas with ultrasound while ocular and prostate/testicular landmarks were the least. Students agreeing to participate in the ultrasound training were highly motivated and described the sessions as valuable for future clinical practice. The evaluation of anatomical knowledge and skills of students following ultrasound training varied widely, and no clear consensus emerged. Long-term assessments of ultrasound-related anatomy competencies were notably underrepresented in the reviewed studies. Conclusions The use of clinical ultrasound in undergraduate anatomy education is implemented through diverse teaching formats and is widely appreciated by medical students. However, standardized methods to assess anatomical understanding of medical students through ultrasound are lacking, impeding the comparison of educational outcomes across studies. Further research is needed to evaluate the long-term retention of skills and knowledge to better determine the effectiveness of ultrasound-based teaching.